Population Projection With The Application of The Differential Equation of The Logistic and Exponential Model (Case Study: Yogyakarta Special Region Province) - Anggreini, Dewi; Sukiyanto, Sukiyanto; Saputra, Bherrio Dwi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
The calculation of population projections in Indonesia at the provincial level is carried out by BPS using the component method, while at the district level it is done using the geometric method with the basic reference of calculating compound interest. From this, it is necessary to take another approach in calculating the projected population in the province of the Special Region of Yogyakarta. This study aims to determine population projections in the Special Region of Yogyakarta using exponential and logistic models based on growth rate and carrying capacity. The data used in this study is secondary data from the Central Bureau of Statistics of the Special Region of Yogyakarta in 2017–2022. The research method used is to determine the research subject, collect data, analyze the data, and draw conclusions. The result of this research is that the carrying capacity of the Special Region of Yogyakarta is 10,652,814 and the population growth rate for the logistic model is 0,02048.